Impact of NaCl, MgCl2 and CaCl2 on seed germination and seedling growth on turnip (Brassica rapa rapa) - Mohammed, Samar Jasim; Nulit, Rosimah (Plant Archives, 2019)
This study was conducted to compare the impact of NaCl, MgCl2 and CaCl2 on the germination of B. rapa rapa seed and seedling growth. Three varieties of salts (NaCl, MgCl2, and CaCl2) at different concentration (25, 50, 75 and 100 mM) and deionized water as control were used. A fifteen sterilized seeds were put in petri dishes containing 5 ml of deionized water or each salinity solution and kept in the growth chamber at twenty one ± 1°C. The experiment is conducted in a completely randomized design with nine replicates. The numbers of germinated seeds were recorded day by day till day tenth. On day 10th, the length of the hypocotyl, radicle and the biomass of seedlings were measured. Germination percentage, seed vigor and salt tolerance were calculated. Data were analyzed using SPSS windows version 21 (one way ANOVA p<0. 05 ) to determine the significant difference between treatment and followed Tukey at p<0.05 for means comparison. Results show the response of B. rapa rapa seed on NaCl, MgCl2, and CaCl2 is completely different. It indicates that the viability of (B. rapa rapa ) seed to germinate relatively high in NaCl followed by CaCl2 and MgCl2.